2021
DOI: 10.5812/ijcm.102610
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Ocimum basilicum and Impatiens walleriana Extracts on AGS and SKOV-3 Cancer Cell Lines by Flow Cytometry Analysis

Abstract: Background: Numerous studies investigate finding new drug candidates with an increasing death rate caused by cancer. Nowadays, herbal medicine has been noticed again because of the many side effects of chemical drugs. Objectives: In the current study, anthocyanin and carotenoid types of compounds of Ocimum basilicum and Impatiens walleriana were determined and their cytotoxic effect on human gastric adenocarcinoma (AGS) and human ovarian carcinoma (SKOV-3) cancer cell lines were investigated. The cytotoxic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, the results reported here agree with those previously reported regarding the highly antiproliferative activity of C. Olitorius leaf extract against Caco-2 cell lines and had a low effect on sk-ov-3 cancer cell lines after treatment at the same concentration (250 µg mL −1 ) [ 6 ]. In another study, it was stated that the compounds in the Ocimum basilicum and Impatiens walleriana extracts suppressed cell viability by more than 78% [ 57 ]. The anticancer effect may be correlated to the higher content of bioactive compounds, which increase the antioxidant effect, rather than the low concentration of dried mallow stem extract.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the results reported here agree with those previously reported regarding the highly antiproliferative activity of C. Olitorius leaf extract against Caco-2 cell lines and had a low effect on sk-ov-3 cancer cell lines after treatment at the same concentration (250 µg mL −1 ) [ 6 ]. In another study, it was stated that the compounds in the Ocimum basilicum and Impatiens walleriana extracts suppressed cell viability by more than 78% [ 57 ]. The anticancer effect may be correlated to the higher content of bioactive compounds, which increase the antioxidant effect, rather than the low concentration of dried mallow stem extract.…”
Section: Resultsmentioning
confidence: 99%
“…Three minutes later, 10 μl of 20 μg/ml propidium iodide solution was added to incubate the cells in the dark for 10 min at room temperature. Finally, an appropriate amount of binding buffer was added for flow cytometry [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was found that in a literature, the aqueous leaf extracts of Rhynchosia suaveolens and Gloriosa superba mediated AgNPs showed potent cytotoxic activity at a concentration (IC 50 ) of 4.2 and 61.80±4.27 µg/ml on SK-OV-3 cell lines [6,50]. Further, it was reported that the ethanolic leaf extract of Ocimum basilicum showed cytotoxicity at a concentration of 5 mg/ml within 72 h with an IC 50 value of 0.91±0.11 mg/ml on SK-OV-3 cell lines [51].…”
Section: Characterization Of Agnpsmentioning
confidence: 96%